Postoperative enterocolitis assessment using two different cut-off values in the HAEC score in Hirschsprung patients undergoing Duhamel and Soave pull-through - Gunadi; Afnandito Valeno Risky Sukarelawanto; Azmi Ritana; Naisya Balela; Wayan Julita Krisnanti Putri; Dian Nirmala Sirait; Vincentia Meta Widya Paramita; Andika Purba Sasmita; Andi Dwihantoro; Akhmad Makhmudi (BMC, 2020)
Abstract Background Hirschsprung-associated enterocolitis (HAEC) is the most severe and potentially lethal complication of Hirschsprung disease (HSCR) which might occur following definitive surgery. Our objectives were: 1) to compare the incidence of HAEC after Duhamel and Soave procedures using different cut-off values of the HAEC scoring method; and 2) to associate them with the risk factors, including sex, aganglionosis type, mothers' age at childbirth, gestational age, and mothers' educational level. Methods Medical records of patients with HSCR who underwent Soave and Duhamel procedures in our institution, Indonesia (January 2012 - December 2016) were reviewed retrospectively. Two cut-off values of the HAEC scoring system (i.e., ≥10 and ≥ 4) were utilized. Results Eighty-three patients with HSCR were recruited in this study (Soave: 37 males and 7 females vs. Duhamel: 28 males and 11 females; p = 0.18). The incidence of HAEC after surgery was 14/83 (16.9%) and 38/83 (45.8%) for cut-off values of ≥10 and ≥ 4, respectively (p = 0.00012), and tended to have an association with sex (p = 0.09). Although it was not statistically significant (p = 0.07), the frequency of HAEC after Soave procedure tended to be higher in patients with their mother's age of ≤35 years at childbirth than those with their mother's age of > 35 years (OR = 7.9; 95% CI = 0.9-72.1). Multivariate analysis indicated none of the risk factors were associated with the frequency of HAEC after definitive surgery. Conclusions The lower cut-off value of ≥4 might increase the possibility to diagnose HAEC, particularly the mild cases. The incidence of HAEC after definitive surgery was not associated with any risk factors in our cohort patients. Further multicenter studies with a larger sample size are necessary to confirm our findings.